BAGAIMANA LOYALITAS TERHADAP HEWLETT PACKARD DI INDONESIA DIBENTUK? - Mursid Dwi Hastomo; Budhi Haryanto (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2018)
This research aims to examine the relationship between product quality, service quality, price and customer satisfaction on customer loyalty. In addition, this research also aims to examine the effect of customer satisfaction as the mediating variable on the customer loyalty establishment process. Survey method selected to collected data. The population used was the customers who intend to be loyal to Hewlett Packard Indonesia branch. The sample was taken using convenience sampling, consisting of 200 respondents. The result of examination using Structural Equation Model (SEM) indicated that there was a positive significant between product quality on customer satisfaction, service quality on customer satisfaction, price on customer satisfaction and customer satisfaction on customer loyalty. The limitation and implication of this research also be discussed to give an understanding to practical aspect, theory and further study.